DEVELOPMENT QUALIFICATION STUDY LAWE PERLAK ROAD – TERUTUNG PAYUNG WITH CONSUMER SURPLUS ANALYSIS - Taufik Taufik; Michel Kasaf, Jetno Harja, Harun Harasid (Adisam Publisher, 2023)
Highway is an accessibility of vehicle users from one region to another to carry out economic, social or cultural movements, increasing the movement of people from one place to another due to population growth and growth in vehicle traffic or other interests, so it requires a highway construction in meeting the demand for human movement in the field of transportation. The purpose of this study is to determine BOK (Vehicle Operating Cost) based on Consumer Surplus Analysis and calculate the economic feasibility of road development (Lawe Perlak – Terutung Payung), when viewed based on Benefit Cost Ratio (BCR), Net Present Value (NPV), and Economic Internal Rate of Return (EIRR). The results of this study get project benefits or vehicle operational cost benefits (BOK) with the consumer surplus method in passenger car types of vehicles amounting to Rp. 3,969, -/vehicle, buses amounting to Rp. 14,977, -/vehicle and for trucks amounting to Rp. 8,566, -/vehicle. And the economic feasibility of the construction of the Lawe Perlak – Terutung Payung (With Project) road in Southeast Aceh district in 2056 or the 37th year after the road is opened, has not met the economic feasibility standards for all discount rates, namely with BCR at a 10% discount rate is 0.75 12% discount rate is 0.62 and at a discount rate 15% is 0.47 then for Net Present Value at a discount rate of 10% obtained NPV Rp.-490,256,465,- discount rate 12% obtained NPV Rp.- 742,010,473,- and at discount rate 15% obtained NPV Rp.- 968,905,014, -.so that the EIRR value is obtained obtained at a discount rate of 91.41%, this shows that the construction of the Lawe Perlak – Terutung Payung (With Project) road is not yet feasible to build, because the interest rate on loans to banks is too large, which is with a value of 91.41%.